2006
DOI: 10.1111/j.1574-6968.1997.tb10232.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient nitrogen and manganese on manganese peroxidase and laccase production by Pleurotus sajor-caju

Abstract: Pleurotus sajor‐caju, strain Pl‐27, produces manganese‐dependent peroxidase (MnP) and laccase, but not lignin peroxidase, when grown on a defined medium with glucose as sole carbon source. MnP activity was detected in fungal cultures supplemented with both high (26 mM‐N) and low (2.6 mM‐N) nutrient nitrogen although higher specific activity values were recorded under the latter conditions. Conversely, laccase production was not influenced by nutrient nitrogen levels under the growth conditions adopted. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…Amino acids or their ramifications are always used as N sources to enhance the laccase activity of white-rot fungi. L-Asparagine can be absorbed directly by organismal cells and participates in metabolic activity (Fu et al 1997;Arora et al 2001;Dhawan et al 2002). Results presented in this paper show that appropriate concentrations of additive N sources could enhance the laccase activity of P. simplicissimum in solid-state fermentation, though the enhancement was not the results of higher fungal biomass.…”
Section: Discussionmentioning
confidence: 73%
“…Amino acids or their ramifications are always used as N sources to enhance the laccase activity of white-rot fungi. L-Asparagine can be absorbed directly by organismal cells and participates in metabolic activity (Fu et al 1997;Arora et al 2001;Dhawan et al 2002). Results presented in this paper show that appropriate concentrations of additive N sources could enhance the laccase activity of P. simplicissimum in solid-state fermentation, though the enhancement was not the results of higher fungal biomass.…”
Section: Discussionmentioning
confidence: 73%
“…For example, 2,6-dimethoxyphenol (SHUTTLEWORTH et al 1986), guaiacol (VARES et al 1995 and ABTS (FU et al 1997, MUÑOZ et al 1997 were all used to detect laccase activity respectively. It has been found in this study that o-tolidine is the best substrate to analyze laccase zymogram while compared with 1,4-diaminobenzene, guaiacol and ABTS.…”
Section: Discussionmentioning
confidence: 99%
“…Laccases are widely distributed among fungi, where they have been assigned roles in lignin degradation (Bourbonnais et al 1995;Eggert et al 1997), in rendering phenolic compounds less toxic via oxidative coupling and polymerisation (Bollag et al 1988; Moldes and Sanroman 2006) and in mushroom fruit-body morphogenesis (Zhao and Kwan 1999;Chen et al 2004). Laccases may be either constitutive or inducible, and many factors including culture parameters (Fu et al 1997), heavy metals (Baldrian and Gabriel 2002;Chen et al 2003) and aromatic compounds (Scheel et al 2000) are reported to influence enzyme production in different fungal species.…”
Section: Introductionmentioning
confidence: 99%